Model Peran Wirausaha dan Dukungan Sosial Untuk Membentuk Minat Berwirausaha di Kalangan Mahasiswa Fakultas Hukum dan Sosial - Darmawan, Didit (ARBITRASE: Journal of Economics and Accounting, 2023)
The high level of dependency on students to get a job immediately after graduating from college has an impact on increasing the unemployment rate. For this reason, so that the conditions that occur can be resolved immediately, an interest in entrepreneurship is needed among students. This research was conducted to observe and analyze the entrepreneurial role model and social support in realizing entrepreneurial intentions among university students. The researcher chose Law and Social Faculty students who were studying at Sunan Giri University in Surabaya to be the research subjects. More specifically, there will be 100 students who will be selected as the research sample using the simple random sampling method. Primary data was obtained from 100 questionnaires distributed to students. The analytical tool used is multiple linear regression using the SPSS program. From the studies that have been carried out, three research results are obtained, namely: (1) there is a partial significant effect of the entrepreneur's role model on student entrepreneurial intentions; (2) there is a significant effect of social support partially on students' entrepreneurial intentions; (3) there is a significant influence simultaneously on the entrepreneurial role model and social support on students' entrepreneurial interest.